Sie sind auf Seite 1von 2

n (m 1 + m 2 ) = n m 1 + n m 2

( m 1 + m 2 ) = n ∗ m 1 + n ∗ m

A(n) A(l), l > n A(n) n, l N

A(n)

A(n) = n (m 1 + m 2 ) = n m 1 + n m 2

m 1 = 1, m 2 = 2 n = 1

A(1) =

1 (1 + 2) = 1 1 + 1 2

= 3

A(n), n = 1 n n n = 1 n n + 1 n + l A(n) A(n + 1) A(n) A(n + l)

A(l)

m 1 = 1, m 2 = 2 l = 2

A(2) =

2 (1 + 2) = 2 1 + 2 2 = 6

A(3)

=

3 (1 + 2) =

3 1 + 3 2

=

9

A(4)

=

4 (1 + 2) =

4 1 + 4 2

=

12

A(5)

=

5 (1 + 2) = 5 1 + 5 2

=

15

A(1000)

=

1000 (1 + 2) = 1000 1 + 1000 2

=

3000

A(n) = n (1 + 2) = n 1 + n 2

A(n) A(l) A(n) A(l) A(n) A(l)[n, l N ; l n]

A(n)